Space-time assessing of the earthquake potential in recent years in the Eastern Anatolia region of Turkey (2017)
In this study, a statistical analysis is carried out to reveal the current earthquake potential in the Eastern Anatolia region of Turkey. For this purpose, a space-time assessing based on the recent changes in Gutenberg-Richter b-value, seismic quiescence Z-value, cumulative moment, annual probability and recurrence time of earthquakes is achieved. Temporal variation of b-value indicates that average b-value decreased from 1.25±0.02 between 2002 and 2010 to 1.08±0.02 between 2011 and 2015. A clear quiescence in the seismic moment in recent years may be a clue foretelling the occurrence of an intense event. Annual probability of the earthquakes between 3.5 and 4.0 magnitude levels exhibits a value equal to and larger than 30. Recurrence time of the earthquakes has a value between 2.0 and 3.0 years for magnitude level of 6.0, and a value between 6.0 and 7.0 years for magnitude level of 7.0. A significant decrease in b-value and clear quiescence anomalies in Z-value at the beginning of 2015 are observed in the several same regions. These areas cover the Central Anatolia Fault Zone, Malatya and Ovacık faults, the southeastern part of the Eastern Anatolia Fault Zone, and the junction of the Eastern Anatolia and Dead Sea Fault Zones. In these anomaly regions, a decreasing trend in b-value may be an indicator of stress increases and an increasing trend in Z-value may show the quiescence areas before the next earthquake occurrences. As a remarkable fact, these areas in the Eastern Anatolia region may be interpreted as one of the most likely locations for the major earthquakes in the future.